Spatial and Time-Course Thermodynamics During Pulmonary Vein Isolation Using the Second-Generation Cryoballoon in a Canine In Vivo Model. (February 2015) - Takami, Mitsuru; Misiri, Juna; Lehmann, H. Immo; Parker, Kay D.; Johnson, Susan B.; Sarmiento, Ray I.; Packer, Douglas L.
Abstract : Background—: Thermodynamics in the left atrium–pulmonary vein (PV) junction, phrenic nerve, and esophagus during PV isolation (PVI) using the second-generation cryoballoon are not known. Methods and Results—: Twenty dogs underwent PVI using second-generation cryoballoon. Ablations were performed for ⩽2 deliveries based on PVI without a bonus freeze. Inner balloon, balloon surface, and tissue temperatures were monitored during cryoablation. The tissue thermocouples were placed on the epicardial surface of the left atrium–PV junction, as well as on the phrenic nerve and within the esophagus. A total of 259 cryoballoon and 229 tissue tissue thermocouples profiles during 53 cryoablations of 40 PVs were analyzed. Acutely, PVI was achieved in 36 of 40 PVs (90%). Conductive tissue cooling spread radially from the balloon–left atrium–PV contact point. The lowest tissue temperatures were dependent on the distance of the tissue thermocouples to the balloon surface ( r =0.85; P <0.001). In addition, blood flow leaks around the balloon had a warming effect on the balloon and tissue temperature profiles. Chronic isolation (mean, 48±16 days) was achieved in 27 of 36 PVs (75%). In 8 of 9 acutely isolated but with chronic reconnection PVs, the blood flow leak location was concordant with chronic reconnection gap. Although only 1 esophageal ulcerated lesion was observed, neither phrenic nerve palsy nor severe PV stenosis was seen in any dogs. Conclusions—: Variance in tissue thermodynamics during cryothermal ablation depends on the distance from balloon and peri-balloon blood flow leaks. This information may be useful for successful PVI without severe complications.